2019
DOI: 10.1093/nar/gkz600
|View full text |Cite
|
Sign up to set email alerts
|

A role for the Saccharomyces cerevisiae ABCF protein New1 in translation termination/recycling

Abstract: Translation is controlled by numerous accessory proteins and translation factors. In the yeast Saccharomyces cerevisiae, translation elongation requires an essential elongation factor, the ABCF ATPase eEF3. A closely related protein, New1, is encoded by a non-essential gene with cold sensitivity and ribosome assembly defect knock-out phenotypes. Since the exact molecular function of New1 is unknown, it is unclear if the ribosome assembly defect is direct, i.e. New1 is a bona fide assembly factor, or indirect, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(48 citation statements)
references
References 78 publications
8
40
0
Order By: Relevance
“…To extend our single codon analysis, we also applied the RiboDiPA pipeline to data collected from yeast lacking New1, a distinct translation termination regulator, which was published by Kasari et al. ( 63 ). NEW1 is a non-essential gene with a cold sensitivity knockout phenotype.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To extend our single codon analysis, we also applied the RiboDiPA pipeline to data collected from yeast lacking New1, a distinct translation termination regulator, which was published by Kasari et al. ( 63 ). NEW1 is a non-essential gene with a cold sensitivity knockout phenotype.…”
Section: Resultsmentioning
confidence: 99%
“… RiboDiPA for single-codon resolution DP analysis: NEW1 deletion ( A ) Single-codon DP analysis of data from ( 63 ), comparing wild type yeast to a NEW1 deletion strain at 20°C. Counts of genes that show DP at a particular codon near the start or stop codon are plotted, with genes with a positive log fold change in the new1Δ condition relative to the WT condition in red, and negative log fold change in cyan.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, the NBD–NBD association appears to be noncanonical in the apo state when dissociated from the ribosome [79]. A typical NBD–NBD sandwich dimer with nucleotide bound is found in the cryo‐EM structure of ribosome‐bound eEF3, implying a major rotation and rearrangement of the NBDs upon ribosome association [79,80]. The linker between the first and second NBDs in eEF3 is similar to the ABCE‐type linker.…”
Section: The Role Of Linkers In Nbd Dimerizationmentioning
confidence: 99%
“…Such approaches are very convenient for analyzing the efficiency of read-through events, but tell nothing about the kinetics and molecular mechanics of the process. Ribosome profiling was recently applied to study termination and stop codon suppression [48,[69][70][71][72][73] and revealed pervasive ribosome occupancy of mRNA regions downstream of stop codons, likely due to defective or regulated ribosome recycling, reinitiation, mRNA degradation, or other processes [74][75][76][77][78][79][80][81]. However, it is also hardly used for analysis of translation dynamics.…”
Section: Introductionmentioning
confidence: 99%